Chromatin Remodeling Protein SMAR1 Is a Critical Regulator of T Helper Cell Differentiation and Inflammatory Diseases - Mirlekar, Bhalchandra; Gautam, Dipendra; Chattopadhyay, Samit (Frontiers in Immunology, 2017)
T cell differentiation from naïve T cells to specialized effector subsets of mature cells is determined by the iterative action of transcription factors. At each stage of specific T cell lineage differentiation, transcription factor interact not only with nuclear proteins such as histone and histone modifiers but also with other factors that are bound to the chromatin and play a critical role in gene expression. In this review, we focus on one of such nuclear protein known as tumor suppressor and matrix attachment region (MAR) binding protein SMAR1 in CD4+ T cell differentiation. SMAR1 facilitates Th1 differentiation by negatively regulating T-bet expression via recruiting HDAC1- SMRT complex to its gene promoter. In contrast, regulatory T cell (Treg) functions are dependent on inhibition of Th17 specific genes mainly IL-17 and STAT3 by SMAR1. Here we discussed a critical role of chromatin remodeling protein SMAR1 in maintaining a fine-tuned balance between effector CD4+ T cells and Treg cells by influencing the transcription factors during allergic and autoimmune inflammatory diseases.